n-Propyl-4-aza-1-azoniabicyclo[2.2.2]octane chloride-SBA-15 (SBA-DABCO) as basic mesoporous catalyst for the synthesis of 1,4-dihydropyridine hetrocyclic compounds - Kiasat, Ali Reza; Davarpanah, Jamal (Catalysis communications, 2015)
Regarding the green chemistry's goals, the development of mesoporous silica materials as attractive candidates in the search for supporting of catalysts is currently a subject of increasing interest. Therefore, in the present research n-propyl-4-aza-1-azoniabicyclo[2.2.2]octane chloride-SBA-15 (SBA–DABCO) was used as a basic catalyst for the synthesis of 1,4-dihydropyridine (DHP) derivatives from one pot, three-component condensation of aromatic aldehydes, ammonium acetate and ethylacetoacetate under solvent-free at 80°C. This method offers several advantages, including high yield, short reaction time, simple work-up procedure, ease of separation and recyclability of the catalyst, as well as the ability to tolerate a wide variety of substitutions in the reagents. •Synthesis of 1,4-dihydropyridine (DHP) derivatives•n-Propyl-4-aza-1-azoniabicyclo[2.2.2]octane chloride-SBA-15 as a basic catalyst•Inorganic–organic hybrid basic nanocatalyst•Green catalyst in the synthesis of biologically relevant heterocyclic compounds